English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-10-02 15:07:48 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

multiply by (2-3i)/(2-3i) 1/(2+3i) *(2-3i)/(2-3i)= (2-3i)/(4-6i+6i-9i^2) which simplifies to (2-3i)/(4+9), which further simplifies to (2-3i)/(13)

2007-10-02 15:16:14 · answer #1 · answered by modenaboy360 3 · 0 0

1/(2+3i)
multiply top and bottom by (2-3i) to get the i out of the denominator

= (2-3i) / (2+3i)(2-3i) = (2-3i) / (2^2 - 9i^2) = (2-3i) / (4 +9) =
(2-3i)/13

2007-10-02 15:13:49 · answer #2 · answered by Steve A 7 · 0 0

fedest.com, questions and answers